Infección por chlamydia trachomatis en pacientes de una institución de salud de Bogotá y Medellín, 2012-2015 (2023)
Introduction: Chlamydia trachomatis presents clinical consequences and it is barely studied in Colombia. Objective: To compare the C. trachomatis infection in Bogotá and Medellín with specific frequencies by gender and age group, between 2012-2015. Methods: Descriptive study of multiple groups, with 1,660 people in Bogotá and 1,087 in Medellin. Anti-Chlamydia trachomatis test with recombinant antigens MOMP, TARP and CPAF was applied; 100% sensitivity and 99.6% specificity. It was estimated and compared the frequency of infection by gender and age group, by hypothesis testing, confidence intervals and prevalence ratios. Results: The largest proportion were women and people between 30-39 years. The frequency of positive IgG in Bogotá was 15.6% (95% CI = 13.4 to 17.8) in Medellin 16.9% (95% CI = 13.4 to 20.4), while the frequency of positive IgM was 0% in Medellin and 0.2% (95% CI = 0.01-1.0) in Bogotá; it was higher in women. In Bogotá, the frequency was higher in younger than 30 years and lower in older than 50. Discussion: The high frequency of infection, its greater occurrence in women, the differences found in the age groups, the low number of investigations in Colombia and clinical risks associated with C. trachomatis, show the need to improve surveillance, screening and research in this infection. © 2016, Sociedad Chilena de Infectologia. All rights reserved.